2014
DOI: 10.1007/s12020-014-0357-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in patients taking selective serotonin reuptake inhibitors: a focus on fracture outcome

Abstract: Depression is one of the most important mental health problems and a leading cause of disability. Selective serotonin reuptake inhibitors (SSRIs) are considered as first-line therapy for the treatment of depressive symptoms among older adults because of their presumed favorable adverse effect profile. However, they could have deleterious effects on the bone. Evidence from longitudinal, cross-sectional, and prospective cohort studies suggests that the use of antidepressants at therapeutic doses is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…These studies further support the notion that serotonin has a deleterious effect on the skeleton, although it cannot be judged if the negative effect is caused by a central or peripheral effects of the 5‐Htt gene deletion or by the administration of the SSRIs. In line with these experimental observations, secondary osteoporosis has been reported to be an off‐target negative effect caused by the use of SSRIs in humans . SSRI users have substantially lower values of serum serotonin compared with non‐SSRI users, as shown in our study as well as by others .…”
Section: Discussionsupporting
confidence: 92%
“…These studies further support the notion that serotonin has a deleterious effect on the skeleton, although it cannot be judged if the negative effect is caused by a central or peripheral effects of the 5‐Htt gene deletion or by the administration of the SSRIs. In line with these experimental observations, secondary osteoporosis has been reported to be an off‐target negative effect caused by the use of SSRIs in humans . SSRI users have substantially lower values of serum serotonin compared with non‐SSRI users, as shown in our study as well as by others .…”
Section: Discussionsupporting
confidence: 92%
“…A recent point prevalence study demonstrated that over one-third of patients admitted to an orthopaedic ward had non-AFs. 30 This association is even more relevant when we consider that depression, as well as antidepressant use, 33 is independently 34 further increasing the risk of fractures in this vulnerable cohort.…”
Section: Discussionmentioning
confidence: 99%
“…SSRIs are considered as first-line therapy for the treatment of depressive symptoms among older adults because of their presumed favorable adverse effect profile [34]. However, serotonin transporters have recently been described in bone [14], raising the possibility that medications that block serotonin reuptake could affect bone metabolism.…”
Section: Discussionmentioning
confidence: 99%